India-Nepal Relation From Nation-Building Perspectives - Karki, Gopal Bahadur (HISAN: Journal of History Association of Nepal, 2022)
Nepal is a landlocked country with a unique national history and geopolitical location between two giant neighbors, India and China. Its relationship with these two nations has had a significant impact on the process of nation-building in Nepal. This article discusses the influence of the changing relationship between Nepal and India on various dimensions of nation-building, using the conceptual framework of Saunders' Research Onion Peeled Method and Harris Mylona and Stein Rokkan's theory of nation-building. The study uses a qualitative approach with phenomenology and historical methods to examine the trends of nation-building around the world and the paradigms of nation-building in Nepal during various periods of its history, including the unification period, the aftermath of the Anglo-Nepal War, the Rana Regime, the Monarchical period, and the aftermath of the end of the monarchy. The research found that internal and external forces, such as globalization and industrialization, as well as geopolitical developments, have had an impact on state nation-building in Nepal.